Title: P2x7 Receptor Activation and Estrogen Status Drive Neuroinflammatory Mechanisms in a Rat Model for Dry Eye - Bereiter, David A.; Rahman, Mostafeezur; Ahmed, Fabeeha; Thompson, Randall; Luong, Nhungoc; Olson, Julie K. (Frontiers in Pharmacology, 2022)
Dry eye disease (DE) is recognized as a chronic inflammatory condition with an increase in tear osmolarity and loss of tear film integrity. DE is often accompanied by adverse ocular symptoms which are more prevalent in females than males. The bases for ocular hyperalgesia in DE remain uncertain; however, both peripheral and central neural mechanisms are implicated. A model for aqueous deficient DE, exorbital gland excision, was used to determine if activation of P2X7R, a purinergic receptor expressed by non-neural cells in peripheral and central trigeminal nerve pathways, and closely linked to inflammatory pain, contributed to persistent ocular hyperalgesia. Densitometry analyses of trigeminal brainstem section revealed increases in P2X7R, Iba1, and NLRP3 of DE females treated with estradiol compared to estrogen-treated sham females, while expression in DE males and DE females not given estrogen displayed only minor changes. No evidence of immune cell infiltration into the trigeminal brainstem was seen in DE rats; however, markers for microglia activation were increased in all groups. Isolated microglia expressed increased levels of P2X7R and P2X4R, IL-1, NLRP3, and iNOS. Further, estrogen-treated DE females displayed greater increases in P2X7R, IL-1 and NLRP3 expression compared to untreated DE females. Orbicularis oculi muscle activity (OOemg) evoked by ocular instillation of hypertonic saline (HS) was recorded as a surrogate measure of ocular hyperalgesia and was markedly enhanced in all DE groups compared to sham rats. Systemic minocycline reduced HS-evoked OOemg in all DE groups compared to sham rats. Local microinjection in the caudal trigeminal brainstem of an antagonist for P2X7R (A804598) greatly reduced HS-evoked OOemg activity in all DE groups, while responses in sham groups were not affected. Microinjection into the trigeminal ganglion of siRNA for P2X7R significantly reduced HS-evoked OOemg activity in all DE groups, while evoked responses in sham animals were not affected. These results indicated that activation of P2X7R at central and peripheral sites in trigeminal pain pathways contributed to an increase in ocular hyperalgesia and microglia activation in DE males and females. Estrogen treatment in females further amplified ocular hyperalgesia and neuroimmune responses in this model for aqueous deficient DE.